Distinct Redox Signalling following Macrophage Activation Influences Profibrotic Activity - Caitlin V. Lewis; Antony Vinh; Henry Diep; Chrishan S. Samuel; Grant R. Drummond; Barbara K. Kemp-Harper (Journal of Immunology Research)
Aims. To date, the ROS-generating capacities of macrophages in different activation states have not been thoroughly compared. This study is aimed at determining the nature and levels of ROS generated following stimulation with common activators of M1 and M2 macrophages and investigating the potential for this to impact fibrosis. Results. Human primary and THP-1 macrophages were treated with IFN-γ+LPS or IL-4-activating stimuli, and mRNA expression of established M1 (CXCL11, CCR7, IL-1β) and M2 (MRC-1, CCL18, CCL22) markers was used to confirm activation. Superoxide generation was assessed by L-012-enhanced chemiluminescence and was increased in both M(IFN-γ+LPS) and M(IL-4) macrophages, as compared to unpolarised macrophages (MΦ). This signal was attenuated with NOX2 siRNA. Increased expression of the p47phox and p67phox subunits of the NOX2 oxidase complex was evident in M(IFN-γ+LPS) and M(IL-4) macrophages, respectively. Amplex Red and DCF fluorescence assays detected increased hydrogen peroxide generation following stimulation with IL-4, but not IFN-γ+LPS. Coculture with human aortic adventitial fibroblasts revealed that M(IL-4), but not M(IFN-γ+LPS), enhanced fibroblast collagen 1 protein expression. Macrophage pretreatment with the hydrogen peroxide scavenger, PEG-catalase, attenuated this effect. Conclusion. We show that superoxide generation is not only enhanced with stimuli associated with M1 macrophage activation but also with the M2 stimulus IL-4. Macrophages activated with IL-4 also exhibited enhanced hydrogen peroxide generation which in turn increased aortic fibroblast collagen production. Thus, M2 macrophage-derived ROS is identified as a potentially important contributor to aortic fibrosis.